The normal inhibition of associations is impaired by clonidine in Tourette syndrome - Kantini, Ebrahim; Cassaday, Helen J.; Hollis, Chris; Jackson, Georgina M. (2011)
Objective: We examined the inhibition of stimulus-stimulus associations (formally ‘conditioned inhibition’) in Tourette syndrome (TS). Method: The present study used video game style conditioned inhibition procedures suitable for children and adolescents. We tested 15 participants with a clinical diagnosis of TS in the absence of co-morbid attention deficit hyperactivity disorder and compared them with 19 typically developing age and sex matched controls (both groups aged 10–20 years). All children were tested for inhibition by summation test using two test stimuli in each of two conditioned inhibition tasks. Results: TS participants showed overall normal inhibition of stimulus-stimulus associations, and there was no correlation between inhibitory learning scores and symptom severity ratings. However, there was a clear reduction in conditioned inhibition in 7 TS participants medicated with clonidine. There was no significant effect of medication on excitatory learning of the stimulus-stimulus associations. Conclusions: We suggest that clonidine’s effect on inhibitory as opposed to excitatory learning could be related to reduced noradrenergic activity. In terms of clinical implications for TS, impaired conditioned inhibition could reduce the ability of susceptible individuals to learn to control tics in the presence of associative triggers.